Suara-Suara Perempuan yang Terbungkam : Analisis Feminisme dalam Gadis Kretek - Rifatus Sholihah; Ahmad Ilzamul Hikam (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
This research aims to analyze the construction of women's roles in the novel Gadis Kretek from a feminist perspective, while simultaneously identifying the representation of silenced women's voices. Employing a descriptive qualitative approach, data in the form of novel text excerpts were analyzed in depth using qualitative content analysis. The novel Gadis Kretek served as the primary data source, with data collection conducted through documentation, involving intensive reading and textual analysis. The researcher acted as the main instrument in this process. Data analysis was performed interactively following the Miles and Huberman model, encompassing data reduction, data display, and conclusion drawing. The research findings reveal diverse structures of silenced women's voices, including patriarchal structures in business and family spheres, social and cultural structures that reinforce women's subordination, narrative and historical structures that disregard women's contributions, and the silencing of emotions, self-agency. This analysis is expected to provide a critical understanding of feminist issues in Indonesian literature.